2009
DOI: 10.5194/acp-9-4973-2009
|View full text |Cite
|
Sign up to set email alerts
|

Sources and transport of Δ<sup>14</sup>C in CO<sub>2</sub> within the Mexico City Basin and vicinity

Abstract: Abstract. Radiocarbon samples taken over Mexico City and the surrounding region during the MILAGRO field campaign in March 2006 exhibited an unexpected distribution:(1) relatively few samples (23%) were below the North American free tropospheric background value (57±2‰) despite the fossil fuel emissions from one of the world's most highly polluted environments; and (2) frequent enrichment well above the background value was observed. Correlate source tracer species and air transport characteristics were examin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
1
22
1
Order By: Relevance
“…difference is probably due to differences in automobile emission systems and fleet ages between the two countries. CO to CO 2 ratios of about 45 ppbv ppmv −1 were observed during the MILAGRO campaign (Vay et al, 2009); a value similar to the ratio observed in plumes originating in China and twice as large as the 10-20 ppbv ppmv −1 observed in industrialized nations like Japan and the United States (de Gouw et al, 2004;Takegawa et al, 2004). It is worth noting, therefore, that VOC emission ratios per kg fuel burned are probably closer to a factor of 6 ± 2 larger in Mexico City than those for US cities.…”
Section: Comparison Of Emission Ratios With Those From Us Citiesmentioning
confidence: 99%
“…difference is probably due to differences in automobile emission systems and fleet ages between the two countries. CO to CO 2 ratios of about 45 ppbv ppmv −1 were observed during the MILAGRO campaign (Vay et al, 2009); a value similar to the ratio observed in plumes originating in China and twice as large as the 10-20 ppbv ppmv −1 observed in industrialized nations like Japan and the United States (de Gouw et al, 2004;Takegawa et al, 2004). It is worth noting, therefore, that VOC emission ratios per kg fuel burned are probably closer to a factor of 6 ± 2 larger in Mexico City than those for US cities.…”
Section: Comparison Of Emission Ratios With Those From Us Citiesmentioning
confidence: 99%
“…Karl et al (2009) estimate 0-10% of the observed aromatic compound concentrations are from biomass burning. Another potential source of information about the relative contribution of anthropogenic and biomass burning emissions is from 14 C isotopic ratio measurements, however interpretation of the results is quite complex due to the contamination of wood by nuclear bomb radiocarbon and other enriched sources (Vay et al, 2009;Aiken et al, 2010). The fraction of fire emissions in the inventory used here (see Table 1) varies greatly among species, depending both on the fire emissions factors and on the magnitude of anthropogenic and natural emissions in this region.…”
Section: Impact Of Mexico City Emissions On Co Distributionsmentioning
confidence: 99%
“…The FZKENDURO Ultialight aircraft was sta tioned at Hermanos Serdan Airport near Huejotzingo, Puebla . The scientific payloads of the three laiger aiicraft are summarized in Table 5 for the C130, Ta ble 6 for the Gl, and Table 2a of Singh et al (2009) for the DC8. The 131 carried mostly radiometric instruments used to measuie aerosols, water vapor, clouds, Eaith surface properties, and radiation fields (see Sect.…”
Section: Intensive Field Studiesmentioning
confidence: 99%
“…Measurements of the spatially varying wind speed, wind direction, temperature, pressure, and humidity over central Mexico were collected by the G-1 , C-130 (de Carlo et al, 2008), DC-8 (Singh et al, 2009), Twin Otter , and the FZK-ENDURO ultralight aircraft . The J-31 ) measured temperature, pressure, and humidity.…”
Section: Observational Resourcesmentioning
confidence: 99%
See 1 more Smart Citation